2019
DOI: 10.1021/acs.est.8b05777
|View full text |Cite
|
Sign up to set email alerts
|

Development of O2 and NO Co-Doped Porous Carbon as a High-Capacity Mercury Sorbent

Abstract: In this study, a novel Hg 0 adsorption strategy based on nonthermal plasma and porous carbon was proposed and tested. The O 2 and NO in flue gas were used to activate porous carbon with auxiliary plasma. The plasma significantly increased the functionalities on the carbon surface, and it has a negligible effect on the textural properties of porous carbon. The O 2 /NO co-doped porous carbon was used to remove elemental mercury (Hg 0 ). The sample functionalized by plasma in 4% O 2 and 200 ppm NO (balanced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Shen et al. [ 69 ] proposed an adsorption method for the removal of Hg 0 using NTP to modify porous carbon (PC). The results showed that, after an O 2 NO/N 2 mixed gas plasma treatment, the elemental mercury (Hg 0 ) adsorption capacity of PC can be increased from 1061 to 12 315 µg g −1 , attributed to the generation of surface functional groups such as CO and CNO, which promoted the interaction between Hg 0 and carbon sites.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Shen et al. [ 69 ] proposed an adsorption method for the removal of Hg 0 using NTP to modify porous carbon (PC). The results showed that, after an O 2 NO/N 2 mixed gas plasma treatment, the elemental mercury (Hg 0 ) adsorption capacity of PC can be increased from 1061 to 12 315 µg g −1 , attributed to the generation of surface functional groups such as CO and CNO, which promoted the interaction between Hg 0 and carbon sites.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Compared with the traditional doping method, the air plasma treatment is a low-cost and ecofriendly method to enhance CO 2 adsorption ability. Furthermore, the high porosity of porous carbon is very attractive for adsorbing radicals during plasma treatment, , which means that more CO 2 adsorption active sites can be generated. However, up to now, no studies were reported for the utilization of air plasma in CO 2 adsorption by porous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be concluded that the chemical adsorption process is the key rate-controlling step for Hg 0 removal in bimetallic FeCu-MOFs. The obtained equilibrium adsorption capacity q e for bimetallic FeCu-MOFs is 12.27 mg/g, which is higher than the commercial brominated activated carbon (1.06 mg/g) 39 and the iron− copper metal oxides modified porous char (2.28 mg/g), 40 indicating that the bimetallic FeCu-MOFs have a great potential for gaseous mercury removal.…”
Section: Resultsmentioning
confidence: 83%
“…This model mainly studies the chemical bond formation and is appropriate for the adsorption process including the chemical adsorption. The inclusive equation for the adsorption rate is shown in eq where t (s) corresponds to the reaction time. q t and q e (μg/g) correspond to the adsorption amount of FeCu-MOFs samples at t and equilibrium time, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%